2012
DOI: 10.1258/ijsa.2011.011331
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of giant condyloma acuminatum with combination retinoid and interferon-γtherapy

Abstract: Giant condyloma acuminatum, or Buschke-Löwenstein tumour, is a unique variant of anogenital warts. It is characterized by locally aggressive behaviour but rarely metastasizes. Many treatment strategies such as radical surgery, radiation and chemotherapy have been used to treat it but their efficacy is often poor and the recurrence rates are high. We report a case of 16-year-old girl who was treated with oral retinoid combined with intramuscular interferon-γ. All lesions cleared within three months. During a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Relatively similar combination therapies, including an immunotherapeutic agent other than Candida antigen (IFN‐α, IFN‐γ, or mycobacterium indicus pranii,) and systemic retinoids (isotretinoin or acitretin) have also been used with success in resistant and recurrent condyloma accuminata …”
Section: Discussionmentioning
confidence: 99%
“…Relatively similar combination therapies, including an immunotherapeutic agent other than Candida antigen (IFN‐α, IFN‐γ, or mycobacterium indicus pranii,) and systemic retinoids (isotretinoin or acitretin) have also been used with success in resistant and recurrent condyloma accuminata …”
Section: Discussionmentioning
confidence: 99%
“…In patients who decline surgery, a biopsy should be performed before initiation of the treatment to confirm the absence of squamous cell carcinoma, although some studies have demonstrated successful treatment of condyloma acuminata with oral retinoid and interferon gamma combination. 14 Cases with giant condyloma acuminata should be verified with computed tomography (CT) or magnetic resonance imaging for the presence of internal organ and lymph node involvement. 12,15,16 In patients with lymph node involvement, lymph node dissection should be performed, and the patient should be kept under oncological control.…”
Section: Discussionmentioning
confidence: 99%
“…A histopathological verification on the line of resection should be mandatory (23). In inoperable cases, radiotherapy, retinoids, interferon-γ and photodynamic therapy can be efficient, but the number of such reports is limited, therefore they are not widely accepted (24,25,26). In severe cases when the bone tissue is affected, amputation is the main therapeutic modality (7,8,19).…”
Section: Discussionmentioning
confidence: 99%